Comparison of retention and denture base adaptation between conventional and 3D-printed complete dentures - Radwa Mohsen Kamal Emera; Mohamed Shady; Mahmoud Almabrouk Alnajih (Tabriz University of Medical Sciences, 2022)
Background. In recent years, complete denture construction has been revolutionized using computer-aided designing and computer-aided manufacturing (CAD-CAM) technology. This clinical study compared the retention and denture base adaptation of 3D-printed complete dentures fabricated using dimethacrylate-based resins with a photoinitiator versus conventional complete dentures. Methods. Ten completely edentulous patients were nominated for this study. Each patient received two complete dentures. One complete denture was conventionally fabricated, while the other was digitally fabricated through 3D printing of dimethacrylate-based resins with a photoinitiator. Denture base adaptation for both dentures was evaluated using surface matching software. Denture retention was also evaluated using a digital force meter at the time of complete denture insertion (T0 ), after three months (T3 ) and six months (T6 ) of denture use. Results. Regarding adaptation (mean misfit values), a statistically insignificant difference was detected between the two differently fabricated complete dentures. In addition, comparable satisfactory retention values were observed for both conventionally fabricated and 3D-printed dentures; however, there was an insignificant increase in retention over time. Conclusion. 3D-printed complete dentures fabricated using dimethacrylate-based resins could be a promising alternative to conventionally fabricated complete dentures with satisfactory denture base adaptation and retention.